Protein body formation in the endoplasmic reticulum as an evolution of storage protein sorting to vacuoles: insights from maize γ-zein - Mainieri, Davide; Morandini, Francesca; Maîtrejean, Marie; Saccani, Andrea; Pedrazzini, Emanuela; Alessandro, Vitale (Frontiers in Plant Science, 2014)
The albumin and globulin seed storage proteins present in all plants accumulate in storage vacuoles. Prolamins, which are the major proteins in cereals seeds and are present only there, instead accumulate within the endoplasmic reticulum (ER) lumen as very large insoluble polymers termed protein bodies. Inter-chain disulfide bonds play a major role in polymerization and insolubility of many prolamins. The N-terminal domain of the maize prolamin 27 kD gamma-zein is able to promote protein body formation when fused to other proteins and contains seven cysteine residues involved in interchain bonds. We show that progressive substitution of these amino acids with serine residues in full length gamma-zein leads to similarly progressive increase in solubility and availability to traffic from the ER along the secretory pathway. Total substitution results in very efficient secretion, whereas the presence of a single cysteine is sufficient to promote partial sorting to the vacuole via a wortmannin-sensitive pathway, similar to the traffic pathway of vacuolar storage proteins. We propose that the mechanism leading to accumulation of prolamins in the ER is a further evolutionary step of the one responsible for accumulation in storage vacuoles.